Species of Conotrachelus (Coleoptera: Curculionidae: Molytinae) associated to the guava and new species description - SALAS-ARAIZA, MANUEL DARÍO; ROMERO-NÁPOLES, JESÚS (Revista Colombiana de Entomología, 2012)
A new species of Conotrachelus is described. It was collected feeding in fruits of Psidium guajava. A key to identify species related to this fruit is included.